Dampak Pembatasan Kampanye Bagi Pemilih Pemula dalam Mendapatkan Informasi Kepemiluan di Masa Pandemi - Robeet Thadi; Poppi Damayanti; Maria Botifar (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
The purpose of this study was to analyze the impact of campaign restrictions for novice voters to obtain electoral information in the 2020 local elections in the midst of the covid-19 pandemic. The research method uses descriptive qualitative research. There are 21 research informants taken from representatives of BEM administrators throughout Bengkulu city, in selecting informants using purposive sampling technique, data obtained through interviews and documentation. The results of the study show a) In limited meetings, one of which is the lack of political education in the community; b) Regarding the rights and disclosure of information, namely: millennial voters are involved in the socialization process, through social media; c) Regarding voter participation, there are assumptions of millennial voters who are still apathetic towards the candidate pair and have an impact on the political confidence of millennial voters. The conclusion of this research is that campaign restrictions will cause limitations in obtaining information about election organizers, election participants, voters and even information about the vision, mission and work program plans offered by pairs of candidates for Pilkada candidates. Keywords: Election Campaign, Election Information, Novice Voters, Pandemic.